Method for improving thermoelectric performance of P-type extruded bismuth telluride-based material
By controlling the particle size and process processing of bismuth telluride-based material powder, the complexity of the performance optimization of P-type materials is solved, and the improvement of the thermoelectric properties of the material and the process simplification are achieved, and it is suitable for mass production.
Patent Information
- Application Number
- CN202411262789.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the performance optimization of P-type bismuth telluride-based materials is complex and has high requirements for molds, making it difficult to ensure the stability of material properties and mass production, and the operation of refining grain size is complicated and difficult to regulate.
By controlling the particle size of bismuth telluride-based material powder within the range of D50>150μm and D90<2000μm, extrusion, sintering and annealing treatment are carried out to ensure the optimal comprehensive performance of the lattice thermal conductivity and mobility of the material, thereby improving the thermoelectric performance .
It achieves the improvement of the thermoelectric performance of the material, ensures the stability of the thermal conductivity of the lattice and texture strength, simplifies the preparation process, and is suitable for mass production.
Smart Images

Figure CN119285357A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermoelectric semiconductor materials, and in particular to a method for improving the thermoelectric performance of a P-type extruded bismuth telluride-based material. Background Art
[0002] Bismuth telluride-based thermoelectric materials are currently one of the thermoelectric materials with the best performance and the most extensive application near room temperature. At present, the commonly used commercial preparation methods are zone melting method and extrusion method. The zone melting method has low performance and poor mechanical properties of the materials prepared, which limits its application in micro-device manufacturing. Extrusion method preparation of materials can not only make the materials obtain stronger texture, but also introduce dynamic recrystallization process at the same time, so that the grains of the materials are further refined, the thermal conductivity of the materials is reduced, and finally better performance is obtained.
[0003] At present, the methods for further improving the performance of thermoelectric materials after the material components are fixed include: improving the electrical properties of the material by strengthening the material texture, refining the grains or introducing nanocomposite phases to reduce the thermal conductivity of the material. Most of the optimization of the performance of P-type materials prepared by the extrusion method is a strategy to reduce the thermal conductivity of the material. The most effective method is to increase phonon scattering to reduce the lattice thermal conductivity, introduce point defects or refine the grain size of the material. The operation of reducing the thermal conductivity of the material by introducing point defects is relatively complicated, and it is difficult to control the material carriers, band structure and other aspects. By refining the grain size, such as a preparation method disclosed in CN117779201A, a hot extrusion method of variable diameter plus torsion extrusion is used to achieve grain refinement, thereby improving the performance of P-type bismuth telluride-based materials, but this method has high requirements for the mold, and the preparation process is also very complicated, and it is difficult to ensure the stability of material performance and mass production.
[0004] Based on this, there is an urgent need for a simple and easily controllable preparation method to reduce the thermal conductivity of P-type extruded materials, increase the orientation strength of the materials, and thus improve the material properties. Summary of the invention
[0005] In order to overcome the problems of complex performance and high requirements on equipment for preparing P-type materials by optimizing the extrusion method, the present invention provides a method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, wherein the particle size of the powder before extrusion is controlled within a reasonable range, and the comprehensive performance of the lattice thermal conductivity and mobility of the bismuth telluride-based materials after extrusion is optimal, thereby improving the thermoelectric performance of the extruded materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for improving the thermoelectric performance of a P-type extruded bismuth telluride-based material comprises the following steps: (1) crushing the bismuth telluride-based material into powder, wherein the particle size range of the powder is D50>150 μm and D90<2000 μm; (2) The powder is pressed into shape, sintered, hot extruded, and annealed to obtain a P-type extruded bismuth telluride-based material.
[0007] Preferably, the bismuth telluride-based material in step (1) is Bi x Sb 2-x Te3, x = 0.3-0.7.
[0008] Preferably, the preparation method of the bismuth telluride-based material in step (1) is: mixing Bi, Sb, and Te raw materials with a purity of ≥99.99% according to a stoichiometric ratio, and smelting them in a vacuum to obtain an ingot.
[0009] As a further preference, Bi, Sb, and Te are placed in a quartz tube in order of melting point or boiling point from low to high, and the tube is sealed so that the pressure inside the tube is less than 2Pa. After being placed in a rocking furnace for rocking smelting for 1-2 hours, the quartz tube is taken out and cooled in air.
[0010] Preferably, the particle size D90 of the powder is 1.8-3.2 times of D50, and the average particle size D50 is maintained at 300-650 μm.
[0011] Preferably, the pulverization is performed using a pulverizer at room temperature without using a ball mill to avoid the introduction of a donor-like effect.
[0012] Preferably, the pulverizer is a stirring pulverizer, and the pulverizing time is controlled within 5 minutes. More preferably, it is a disc crusher.
[0013] Preferably, the compression molding is carried out at room temperature and the pressure is 150-200 MPa.
[0014] Preferably, the sintering is vacuum sintering, the sintering temperature is 500-600° C., and the sintering time is 5-15 hours.
[0015] Preferably, the extrusion temperature is 300-500°C, the pressure is 100-300 MPa, and the die extrusion deformation is 9-27.
[0016] Preferably, the annealing temperature is 300-400° C. and the annealing time is 5-15 h.
[0017] Therefore, the beneficial effects of the present invention are as follows: because the extrusion process will cause a deformation process on the material, the degree of thermal conductivity reduction is certain. By controlling the particle size of the powder before extrusion, it is clear that when the particle size of the powder is between 300μm≤D50≤650μm and D90 is 1.8-3.2 times of D50, the lattice thermal conductivity of the material no longer changes significantly, that is, the grain size corresponding to the scattering limit of short-frequency long-wave phonons. While ensuring that the lattice thermal conductivity does not change, the increase in particle size can effectively improve the material texture strength, thereby improving the material mobility to improve the electrical properties, and then improve the thermoelectric properties of the extruded material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a grain morphology diagram of P-type extruded bismuth telluride-based material; in the figure, a corresponds to comparative example 1, b corresponds to example 1, c corresponds to example 2, and d corresponds to example 3.
[0019] Figure 2 It is the total thermal conductivity diagram and lattice thermal conductivity diagram of the products of Examples 1, 2, 3 and Comparative Example 1; in the figure, a is the total thermal conductivity diagram, and b is the lattice thermal conductivity diagram.
[0020] Figure 3 These are the Seebeck diagrams and conductivity diagrams of the products of Examples 1, 2, 3 and Comparative Example 1; in the figure, a is the Seebeck diagram and b is the conductivity diagram.
[0021] Figure 4 It is the thermoelectric figure of merit of the products of Examples 1, 2, 3 and Comparative Example 1. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below through specific embodiments.
[0023] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.
[0024] Example A method for improving the thermoelectric performance of a P-type extruded bismuth telluride-based material comprises the following steps: (1)Material synthesis Bi, Sb, Te according to the stoichiometric ratio Bi x Sb2-x Te3 is weighed (x=0.3-0.7, purity ≥99.99%), and is placed into a quartz tube in order of melting point or boiling point from low to high. After sealing the tube, the pressure inside the tube is less than 2Pa. After being placed in a rocking furnace for rocking melting for 1-2 hours, the quartz tube is taken out and cooled in the air.
[0025] (2) Powder crushing The material synthesized in step (1) is crushed at room temperature using a crusher. In order to avoid the introduction of a donor-like effect, a stirring crusher (such as a disc crusher) is selected, the crushing time is controlled within 5 minutes, and the powder particle size is controlled within the mesh range of D50>150μm and D90<2000μm. It is further preferred that the powder particle size range is controlled within 300≤D50≤650μm and D90<2000μm, while ensuring that D90 is 1.8-3.2 times of D50.
[0026] Among them, D50 (median value) indicates the corresponding particle size when the cumulative distribution in the system accounts for 50%, and can also represent the average particle size; D90 (peak value) indicates the corresponding particle size when the cumulative distribution in the system accounts for 90%. The larger the value of D90 / D50, the larger the proportion of larger particles in the powder, and the smaller the proportion of smaller particles. The presence of larger particles will destroy the overall uniformity. On the contrary, the smaller the value of D90 / D50, the more concentrated the particle size distribution in the powder, and the size of most particles is close to the value of D50. Such powder has better uniformity.
[0027] (3) Powder processing The powder obtained in step (2) is pressed into a shape at room temperature with a pressing strength of 150-200 MPa, and then the blank is placed in a heating furnace at a temperature of 500-600° C. for vacuum sintering with a sintering time of 5-15 hours.
[0028] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100-300 MPa is applied to the material at a high temperature of 300-500° C. The material is extruded along the die outlet direction, and the extrusion ratio of the die is 9-27, thereby obtaining a P-type extruded material.
[0029] (5) Annealing The material obtained in step (4) is annealed in vacuum at 300-400° C. for 5-15 h to obtain a P-type extruded bismuth telluride-based material.
[0030] Example 1 A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0031] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature for 4 minutes using a disc crusher to obtain a powder with a particle size of D50 = 330 μm and D90 = 650 μm.
[0032] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0033] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0034] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0035] Example 2 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=500μm and D90=1000μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0036] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 500 μm and D90 = 1000 μm.
[0037] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0038] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0039] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0040] Example 3 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=650μm and D90=1700μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0041] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 650 μm and D90 = 1700 μm.
[0042] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0043] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0044] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0045] Example 4 A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.3 Sb 1.7 Weigh Te3; put it into a quartz tube in order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 2h, then take out the quartz tube and cool it in the air.
[0046] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature for 5 minutes using a disc crusher to obtain a powder with a particle size of D50 = 330 μm and D90 = 650 μm.
[0047] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 150 MPa. The blank was then placed in a heating furnace at 600° C. for vacuum sintering for 5 hours.
[0048] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 300 MPa is applied to the material at a high temperature of 300° C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 9, thereby obtaining a P-type extruded material.
[0049] (5) Annealing The material obtained in step (4) was annealed at 300° C. in vacuum for 15 h.
[0050] Example 5 A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.7 Sb 1.3 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0051] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature for 4 minutes using a disc crusher to obtain a powder with a particle size of D50 = 330 μm and D90 = 650 μm.
[0052] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 550° C. for vacuum sintering with a sintering time of 15 h.
[0053] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 200 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 27, thereby obtaining a P-type extruded material.
[0054] (5) Annealing The material obtained in step (4) was annealed at 400° C. in vacuum for 5 h.
[0055] Example 6 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=330μm and D90=500μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0056] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 330 μm and D90 = 500 μm.
[0057] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0058] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0059] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0060] Example 7 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=330μm and D90=1320μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0061] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 330 μm and D90 = 1320 μm.
[0062] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0063] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0064] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0065] Comparative Example Comparative Example 1 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=150μm and D90=400μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0066] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 150 μm and D90 = 400 μm.
[0067] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0068] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0069] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0070] Comparative Example 2 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=16μm and D90=60μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, the steps are as follows: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0071] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 16 μm and D90 = 60 μm.
[0072] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0073] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0074] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0075] Comparative Example 3 The difference from Example 1 is that the particle size of the powder after crushing in step (2) is D50=650μm, D90=3000μm. Specifically: A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, comprising the following steps: (1)Material synthesis Bi, Sb, Te with purity ≥99.99% are added according to the stoichiometric ratio Bi 0.5 Sb 1.5 Weigh Te3; put it into a quartz tube in the order of melting point or boiling point from low to high, seal the tube so that the pressure inside the tube is less than 2Pa, put it into a rocking furnace at 700℃ for rocking melting for 1h, then take out the quartz tube and cool it in the air.
[0076] (2) Powder crushing The material synthesized in step (1) was crushed at room temperature using a disc crusher to obtain a powder with a particle size of D50 = 650 μm and D90 = 3000 μm.
[0077] (3) Powder processing The powder obtained in step (2) was pressed into a shape at room temperature with a pressing strength of 200 MPa, and then the blank was placed in a heating furnace at a temperature of 500° C. for vacuum sintering with a sintering time of 15 h.
[0078] (4) Hot extrusion The blank obtained in step (3) is loaded into an extrusion die, and a pressure of 100 MPa is applied to the material at a high temperature of 400°C. The blank is extruded along the die outlet direction, and the extrusion ratio of the die is 15, thereby obtaining a P-type extruded material.
[0079] (5) Annealing The material obtained in step (4) was annealed at 360° C. in vacuum for 10 h.
[0080] Performance Testing The properties of the P-type extruded bismuth telluride-based materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were tested under the following conditions and methods: (1) The total thermal conductivity is calculated by κ = DρC p Calculated, where ρ is the material density measured by the displacement method, C p The specific heat is calculated by the Dulong–Petit law, and D is measured by the Netzsch LFA467 equipment; (2) lattice thermal conductivity κ l is through κ l =κ-κ eCalculated; (3) Electrical conductivity and Seebeck coefficient: Electrical conductivity and Seebeck coefficient are measured using the ZEM-3 device; (4) Thermoelectric figure of merit zT is calculated by zT = ασT / κ. The results are as follows Figure 1-Figure 4 shown.
[0081] Figure 1 is the grain morphology diagram, from Figure 1 It can be seen that: the powder particle size of comparative example 1 before extrusion is the smallest, and its grain size is the smallest. As the powder particle size of examples 1, 2, and 3 gradually increases, the grain size will increase accordingly. From example 2 to example 3, the increase in grain size is not obvious.
[0082] Figure 2 is the total thermal conductivity map and the lattice thermal conductivity map, from Figure 2 It can be seen that as the particle size of the powder before extrusion gradually increases, its thermal conductivity also gradually increases, because as the material mobility increases, the electrical conductivity increases. However, from the test results of lattice thermal conductivity, comparing Comparative Example 1 and Example 1, as the size gradually increases, the lattice thermal conductivity remains basically unchanged. When the powder particle size is further increased, the lattice thermal conductivity curves of Example 2 and Example 3 are basically overlapped, and relative to Comparative Example 1, the lattice thermal conductivity change rate is less than 2%.
[0083] Figure 3 is the Seebeck diagram and the conductivity diagram, from Figure 3 It can be seen that: comparing comparative example 1 with embodiments 1 and 2, as the particle size of the powder before extrusion gradually increases, the Seebeck coefficient remains basically unchanged, indicating that the donor-like effect introduced by pulverizing under air has little effect on the carrier concentration of the material within this particle size range, and its conductivity is gradually increasing. The main reason is that the texture strength of the material increases, resulting in an increase in mobility. From embodiments 2 and 3, it can be seen that when the size is further increased, the increase in its conductivity is also very small, and the Seebeck is slightly reduced, indicating that as the particle size gradually increases to the limit, the increase in its mobility is also approaching the limit, and the donor-like effect introduced by pulverizing under air has no effect on it, and the carrier concentration is slightly higher than that of embodiments 1 and 2.
[0084] Figure 4 is the thermoelectric figure of merit, from Figure 4 It can be seen that: comparing comparative example 1 with embodiments 1 and 2, as the particle size of the powder before extrusion gradually increases, its performance gradually increases, and the improvement is greater than 10%. It can be seen from embodiments 2 and 3 that there is also a limit to the improvement of the mobility by the powder particle size, and as it further increases, its performance will decrease.
[0085] The thermoelectric figures of merit (zT) of the P-type extruded bismuth telluride-based materials prepared in the embodiments and comparative examples are further compared, and the results are shown in the following table.
[0086] It can be seen from the above table that the P-type extruded bismuth telluride-based materials prepared in various embodiments of the present invention have excellent thermoelectric properties.
[0087] Compared with Example 1: (1) The lattice thermal conductivity of the material in Comparative Example 1 is not much different, but the particle size is lower than the preferred range, resulting in reduced material mobility, reduced electrical conductivity, and decreased thermoelectric figure of merit.
[0088] (2) In Example 6 and Example 7, both D50 and D90 are within the preferred range, but D90 / D50 is not within the preferred range. The D90 / D50 of Example 6 is lower than the preferred range, and the particle size uniformity is better. However, the present invention requires a certain particle size difference, which is beneficial to the improvement of the thermoelectric figure of merit. Specifically, the lattice thermal conductivity is not significantly improved, but it is not conducive to the improvement of the material electrical conductivity, and the final thermoelectric figure of merit is reduced. The D90 / D50 value of Example 7 is higher than the preferred range, the large particle size accounts for a large proportion, and the uniformity is poor, resulting in the lattice thermal conductivity starting to increase, while the electrical conductivity improvement reaches the limit, and the final thermoelectric figure of merit is not good.
[0089] (3) The particle size and D90 / D50 values of Comparative Examples 2 and 3 are not within the preferred range, and the particle size range is too large, exceeding the particle size range where the lattice thermal conductivity is stable, resulting in a significant increase in the lattice thermal conductivity of the material. At the same time, the electrical conductivity is not significantly improved, resulting in a significant decrease in the thermoelectric figure of merit.
[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials, characterized in that: The following steps are involved: (1) Grinding the bismuth telluride-based material into powder, wherein the particle size range of the powder is D50 > 150 μm and D90 < 2000 μm; (2) The powder is pressed into shape, sintered, hot extruded, and annealed to obtain a P-type extruded bismuth telluride-based material.
2. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1, characterized in that: Bismuth telluride-based materials are Bi x Sb 2-x Te3, x=0.3-0.
7.
3. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1 or 2, characterized in that: The preparation method of bismuth telluride-based materials is as follows: Bi, Sb, and Te raw materials with a purity of ≥99.99% are mixed according to a stoichiometric ratio, and smelted in a vacuum to obtain an ingot.
4. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 3, characterized in that: Bi, Sb, and Te are placed in a quartz tube in order of melting point or boiling point from low to high. After sealing the tube, the pressure inside the tube is less than 2Pa. After placing it in a rocking furnace for rocking melting for 1-2 hours, the quartz tube is taken out and cooled in the air.
5. The method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1, characterized in that: The particle size D90 of the powder is 1.8-3.2 times of D50, and the average particle size D50 is 300-650 μm.
6. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1 or 5, characterized in that: The powder was crushed using a crusher at room temperature.
7. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1, characterized in that: The compression molding is carried out at room temperature and the pressure is 150-200 MPa.
8. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1 or 7, characterized in that: The sintering is vacuum sintering, the sintering temperature is 500-600 ℃, and the time is 5-15 h.
9. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1, characterized in that: The extrusion temperature is 300-500 ℃, the pressure is 100-300 MPa, and the die extrusion deformation is 9-27.
10. A method for improving the thermoelectric performance of P-type extruded bismuth telluride-based materials according to claim 1 or 9, characterized in that: The annealing temperature is 300-400 ℃ and the time is 5-15 h.
Citation Information
Patent Citations
P-type bismuth telluride-based thermoelectric material and preparation method and application thereof
CN113889563A
Hot extrusion forming method of bismuth telluride thermoelectric material
CN114210978A
Method for improving performance uniformity of hot-extruded N-type bismuth telluride
CN115305567A
Preparation method for improving thermoelectric performance of extruded material
CN115815600A
Preparation method of bismuth telluride thermoelectric material containing graphene
CN117794344A
Cited By
A p-type bismuth telluride-based thermoelectric material and a method for preparing the same
CN122935126A